Por uma história das "Lojas com História" : o caso da Farmácia Barreto - Freitas, Luís Miguel Correia (2020)
In 2015, the Lisbon city council announced the establishment of a pioneer project for the protection of traditional commerce, called “Lojas com História” (shops with history). Considering the traditional shops as a distinctive element of the city, the project intended to create ways to maintain their sustainability and their presence, through their recognition and by adding value to these places that are gradually disappearing. On this Museology and Museography master thesis, we intend to present the whole project, using Farmácia Barreto a case study. With this purpose, we begin our work by presenting the project’s idea, mentioning the criteria that define the different items for the shops’ classification, the multiple teams involved in its development and the municipal funding assigned to works of preservation and restoration of the shops’ elements. Secondly, we present other initiatives with the same characteristics that have been developed in different Portuguese cities, showing how this project in Lisbon has become a reference in the maintenance of traditional commerce in Portugal. Facing the possibility of considering Farmácia Barreto as a living museum or as a branch of Museu da Farmácia, we develop some reflections about integrated heritage and specifically about the Portuguese law (Lei n.º 42/2017) that has introduced important measures to protect traditional commerce, creating a prosperous environment through the introduction of benefits to the owners, tenants and, above all, to the shops themselves. In the final part, we dedicate a chapter of this work to our case study, the Farmácia Barreto, which has been part of the first group of classified shops of the “Lojas com História” project. We intend to present the history of this centenary place, highlighting the owner’s opinion on the importance of the project to the city, and specifically the impact on his business, showing his concerns about the sustainability of this pharmacy by looking at it as a living museum.